Making the News Popular : Mobilizing U.S. News Audiences - Nadler, Anthony M., 1978- (Book collections on Project MUSE., 2016)
"Making the News Popular critically examines the shift from a high modern era to a post-professional era in U.S. news culture. For high modern journalism of the mid-20th century, professional judgment served as the basis for defining the news agenda. Yet even before the rise of digital journalism, U.S. news organizations began embracing a very different editorial philosophy - one positioning consumer demand as the most legitimate basis for defining news. For its advocates, demand-driven news represents a democratization of the media, allowing ordinary citizens rather than a professional elite to determine the priorities and boundaries of news. Nadler shows the continuity in this line of thinking from the influx of market research into newspapers in the late 1970s through contemporary experiments in collaborative filtering and social news sites such as Reddit and Digg. Yet, idealized visions of demand-driven news have faced similar problems with each iteration. While exploring the historical pull of this editorial philosophy, Nadler also shows how it fails to recognize the role news organizations play in mobilizing popular interest in news and public life. News organizations attempting to simply "give people what they want" also end up devoting resources to mobilizing particular kinds of public interest in and demand for news. He argues this underappreciated civic role of news organizations requires greater attention in today's discussions of the future of news if journalism's digital crisis is to lead to a more robust and democratic news media"--